2019
DOI: 10.1016/j.renene.2018.07.140
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the potential for energy flexibility in an office building with a vertical BIPV and a PV roof system

Abstract: Building Integrated Photovoltaics (BIPV) are becoming an attractive solution in the context of high penetration of photovoltaics (PV) in buildings caused by the strive to achieve net or nearly zero energy status. Besides retrieving solar radiation to produce electricity, BIPV also offers aesthetical advantages because of its architectural feature. This paper reports on the electrical energy performance of a passive solar office building, Solar XXI, located in Lisbon, Portugal, which has installed on the South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…The payback ratio value of the system was calculated for time steps of five minutes based on electric energy meters' readings every 30 s [9]. Aelenei et al investigated the electricity generation performance of 12-kWp installed power on the south facade a building integrated photovoltaic (BIPV) and an additional 12-kWp PV roof system in a nearby car park facility for office buildings at the National Laboratory of Energy and Geology (LNEG), in Portugal [10]. Dondariya et al [11] focused on feasibility analysis of grid-connected rooftop solar photovoltaic system (RSPS) at Ujjain Engineering College, in India.…”
Section: Introductionmentioning
confidence: 99%
“…The payback ratio value of the system was calculated for time steps of five minutes based on electric energy meters' readings every 30 s [9]. Aelenei et al investigated the electricity generation performance of 12-kWp installed power on the south facade a building integrated photovoltaic (BIPV) and an additional 12-kWp PV roof system in a nearby car park facility for office buildings at the National Laboratory of Energy and Geology (LNEG), in Portugal [10]. Dondariya et al [11] focused on feasibility analysis of grid-connected rooftop solar photovoltaic system (RSPS) at Ujjain Engineering College, in India.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have carried out the performance studies on the BIPV system, and their focus was mostly on the BIPV roof or the facades [2,3,5,6,[25][26][27]32]. A study by Aristizábal and Páez [5] showed the operational performance of 6 kW BIPV system installed in Colombia (in Bogotá, at 4°35′ latitude and 2.580 m altitude), and their investigation highlights the AC energy (471,083 kWh/month), final yield (88.6 kWh/kWp-year).…”
Section: Introductionmentioning
confidence: 99%
“…It was highlighted that the performance efficiency of the DSSC BIPV is quite higher in the vertical plane than the sloped plane. The performance of two 12 kWp BIPV systems, one installed on the south façade, and the other as the roof, is investigated in Aelenei et al [2]. Akata et al [3] reported the potentials of BIPV in the tropical region of Cameron.…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that, photovoltaics can provide the required energy consumption of the studied building and the payback period is smaller than seven years. Passive office facility situated Portugal is examined by Aeleni et al [13]. Actual consumption data are employed together with numerical simulations of integrated battery storage system.…”
Section: Introductionmentioning
confidence: 99%